Effect of carbon on whole-biofilm metabolic response to high doses of streptomycin - Jackson, Lindsay; Kroukamp, Otini; Wolfaardt, Gideon (Frontiers in Microbiology, 2015)
Biofilms typically exist as complex communities comprising multiple species with the ability to adapt to a variety of harsh conditions. In clinical settings, antibiotic treatments based on planktonic susceptibility tests are often ineffective against biofilm infections. Using a CO2 evolution measurement system we delineated the real- time metabolic response in continuous flow biofilms to streptomycin doses much greater than their planktonic susceptibilities. Stable biofilms from a multispecies culture (containing mainly Pseudomonas aeruginosa and Stenotrophomonas maltophilia), Gram-negative environmental isolates, and biofilms formed by pure culture P. aeruginosa strains PAO1 and PAO1 ΔMexXY (minimum planktonic inhibitory concentrations between 1.5-3.5 mg/l), were exposed in separate experiments to 4000 mg/l streptomycin for 4 h after which growth medium resumed. In complex medium, early steady state multispecies species biofilms were susceptible to streptomycin exposure, inferred by a cessation of CO2 production. However, multispecies biofilms survived high dose exposures when there was extra carbon in the antibiotic medium, or when they were grown in defined citrate medium. The environmental isolates and PAO1 biofilms showed similar metabolic profiles in response to streptomycin; ceasing CO2 production after initial exposure, with CO2 levels dropping towards baseline levels prior to recovery back to steady state levels, while subsequent antibiotic exposure elicited increased CO2 output. Monitoring biofilm metabolic response in real-time allowed exploration of conditions resulting in vulnerability after antibiotic exposure compared to the resistance displayed following subsequent to further exposures.